Southern African Perspectives on Sustainable Tourism Management Tourism and Changing Localities - Saarinen, Jarkko; Lubbe, Berendien; Moswete, Naomi N. (Cham : Springer International Publishing : Imprint: Springer, 2022)
This edited collection focuses on tourism development, sustainability and local change in southern Africa. The book offers a range of both conceptual and applied perspectives that address various changes in southern African tourism and community development relations. The key drivers of change that include climate change and globalization form the context for the diverse and interesting set of case studies from the region. The main conceptual grounds of the book cover sustainability, sustainable development goals (SDGs), responsibility, vulnerability, adaptation, resilience, governance, local development and inclusive growth. In this book sustainability is seen as one of the most important issues currently facing the tourism sector, affecting all types and scales of tourism operations and environments in the region. Tourism is an increasingly important economy in the southern African region and the industry is creating changes for communities and environment while also facing major challenges caused by global trends and changes. The book offers a case study driven approach to sustainability needs of tourism development in local community contexts. The case study chapters are linked through the book's focus on sustainable tourism and local community development. Through emphasizing the need to understand both global change and local contexts in sustainable tourism development, this book is a valuable resource for all those working in the field.
1. Sustainable Tourism Development in the Southern African Context: An Introduction (Jarkko Saarinen, Berendien Lubbe and Naomi Moswete) -- 2. Sustainability Consciousness in the Hospitality Sector in Zimbabwe (Ngoni Courage Shereni, Jarkko Saarinen and Christian M. Rogerson) -- 3. In Pursuit of Sustainable Tourism in Botswana: Perceptions of Maun Tourism Accommodation Operators on Tourism Certification and Eco-labelling (Godiraone T. Motsaathebe and Wame L. Hambira) -- 4. Inbound Tour Operator Participation in Sustainable Tourism Practices: A Focus on South Africa (Ignatius Ludulph Steyn, Felicite Fairer-Wessels and Anneli Douglas) -- 5. Tourism-led Inclusive Growth Paradigm: Opportunities and Challenges in the Agricultural Food Supply Chain in Livingstone, Zambia (Brenda Nsanzya & Jarkko Saarinen) -- 6. Insourcing the Indigenous without Outsourcing the Story Teller: A sustainable African Solution (Karen L Harris & Christoffel R Botha) -- 7. Assessment of Costs and Benefits of Joint Venture Partnerships in Community-based Tourism between the Private Sector and Goo-Moremi Residents, Botswana (Bontle Elijah, Naomi Moswete and Masego Mpotokwane) -- 8. Socio-economic Impacts of Community-based Ecotourism on Rural Livelihoods: A Case Study of Khawa Village in the Kalahari Region, Botswana (Naomi Moswete, Jarkko Saarinen and Brijesh Thapa) -- 9. Community-based Tourism as a Pathway Towards Sustainable Livelihoods and Well-being in Southern Africa (Alinah K. Segobye, Maduo Mpolokang, Ngoni C. Shereni, Stephen Mago and Malatsi Seleka) -- 10. Changing Environment and the Political Ecology of Authenticity in Heritage Tourism: A Case of the Ovahimba and the Ju/'Hoansi-San Living Museums in Namibia (Isobel Green and Jarkko Saarinen) -- 11. Perspectives on the Applicability of Nexus Thinking to Private Protected Areas: A Case Study of Mokolodi Nature Reserve, Botswana (James Maradza, Raban Chanda and Naomi Moswete) -- 12. Environmental Change, Wildlife-based Tourism and Sustainability in Chobe National Park, Botswana (Maduo O. Mpolokang, Jeremy S. Perkins, Jarkko Saarinen and Naomi Moswete) -- 13. The Impact of rhino Poaching on the Economic Dimension of Sustainable Development in Wildlife Tourism (Berendien Lubbe) -- 14. Locational Heterogeneity in Climate Change Threats to Beach Tourism Destinations in South Africa (Jonathan Friedrich, Jannik Stahl, Gijsbert Hoogendoorn and Jennifer M. Fitchett) -- 15. Sustainable Tourism Development needs in the Southern African Context: Concluding Remarks (Jarkko Saarinen, Naomi Moswete and Berendien Lubbe).
Keywords: Human geography; Human ecology-Study and teaching; Environmental sciences-Social aspects; Human Geography; Environmental Studies; Environmental Social Sciences